Chondroitin sulfate/dermatan sulfate from corb (Sciaena umbra) skin: Purification, structural analysis and anticoagulant effect. (15th September 2018) - Bougatef, Hajer; Krichen, Fatma; Capitani, Federica; Amor, Ikram Ben; Maccari, Francesca; Mantovani, Veronica; Galeotti, Fabio; Volpi, Nicola; Bougatef, Ali; Sila, Assaad
Highlights: Chondroitin sulfate/dermatan sulfate was purified from skin of corb (CSG). The chemical and structural analyses of CSG were studied. CSG has high sulfate content and a relatively low molecular mass. CSG exhibited significant anticoagulant effect. Abstract: In this study, chondroitin sulfate/dermatan sulfate was isolated and purified from the skin of corb ( Sciaena umbra ) (CSG) with a yield of 6.2%. Chemical and structural analysis showed that CSG consisted of high sulfate content 28.74% and an average molecular weight of 15.46 KDa. The separation of CSG by agarose-gel electrophoresis revealed the presence of DS and CS. Structural analysis of the purified CS/DS by means of SAX–HPLC after treatment with specific chondroitinases showed that this polymer was composed of nonsulfated disaccharide, monosulfated disaccharides and disulfated disaccharides in various percentages. The results also suggest that the percentage of CS and DS recovred in CSG were 24% and 76%, respectively. Anticoagulant activity in vitro was measured in plasma using classical anticoagulation tests: activated partial thromboplastin time (aPTT), thrombin time (TT) and prothrombine time (PT) tests. The findings thus indicated that the purified CS/DS exhibits a remarkably high anticoagulant effect.